2002
DOI: 10.4269/ajtmh.2002.66.794
|View full text |Cite
|
Sign up to set email alerts
|

Hyperendemic Cryptosporidium and Giardia in households lacking municipal sewer and water on the United States-Mexico border.

Abstract: Abstract. This study identified differences in the epidemiology of Giardia and Cryptosporidium infection for lowincome populations residing on the United States-Mexico border. Participation included 77 households in three communities lacking adequate municipal water and sewage services. The household was the unit of analysis and sampling was from household biosolid waste from newly installed composting toilets. The proportion of households positive for Giardia and Cryptosporidium was high, 82% and 70%, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 14 publications
3
25
1
6
Order By: Relevance
“…This lack of infrastructure results in polluted environments and more hazardous behaviors that increase the rate of disease and injury for thousands of Juárez residents [15]. Redlinger et al (2002) found that the proportion of households living in the peri-urban region of Ciudad Juárez and positive for Giardia and Cryptosporidium was high, 82% and 70% respectively [17]. According to the Cd.…”
Section: Ciudad Juárez Méxicomentioning
confidence: 99%
“…This lack of infrastructure results in polluted environments and more hazardous behaviors that increase the rate of disease and injury for thousands of Juárez residents [15]. Redlinger et al (2002) found that the proportion of households living in the peri-urban region of Ciudad Juárez and positive for Giardia and Cryptosporidium was high, 82% and 70% respectively [17]. According to the Cd.…”
Section: Ciudad Juárez Méxicomentioning
confidence: 99%
“…To read the DAPI, we used a 365-400 nm excitation filter and a 395 nm emission filter (REDLINGER et al, 2002). To identify oocysts and cysts, we used an immunofluorescence defined by a bright apple-green color, the absence of pores or appendices that had a compatible size and format: 8-12 µm in size and an oval shape for Giardia spp.…”
Section: Direct Immunofluorescence Testmentioning
confidence: 99%
“…and 3-8.5 µm in diameter, a spherical shape and the presence (not necessary) of sutures in the oocyst for Cryptosporidium spp. (REDLINGER et al, 2002).…”
Section: Direct Immunofluorescence Testmentioning
confidence: 99%
“…The wild and domestic animals can be host in nature. It is estimated that 0.6 to 4.3% of the world's population infected with Cryptosporidium [4].…”
Section: Introductionmentioning
confidence: 99%